Problemy rozwoju przedsiębiorczości w warunkach integracji europejskiej - Zioło, Zbigniew (Przedsiębiorczość - Edukacja, 2010)
Increasingly intensified processes of globalization and the connected processes of European integration create new challenges for particular individuals and societies, and also business entities and institutions that are present in various scales of spatial systems. They refer to the rules of progressing process of concentration of capital (business activity) which results in the emergence of larger and larger global corporations. Their activities intensify polarization of global, European, national or regional social, economic and cultural space, and to some extent they lead to their standardization. That is why aspiring to learn complex regularities of changes that happen both in companies, and in particular spatial systems is so crucial during the process of development managing. Thus, it is advised to remember that problems concerning development of businesses, which refer both to the way of managing an enterprise as well as to spatial systems, are of great importance and they are part of current research subjects in the area of theoretical inquiries and within the scope of development of empirical analyses. They lead to more precise cognition of mechanisms and determinants, which in domestic conditions should be used to activate society within the range of developing resourcefulness. A model, which can serve as a pattern to conduct analyses and construct strategies of development of particular categories of companies and their surroundings, with attention paid to the impact of such features as: institutions and members of the EU, markets, economic policy and potential alternatives concerning behaviour of decision-makers of any kind, was proposed in this paper.